With low ovarian reserve, Highly Individualized Egg Retrieval (HIER) improves IVF results by avoiding premature luteinization - Yan-Guang Wu; David H. Barad; Vitaly A. Kushnir; Qi Wang; Lin Zhang; Sarah K. Darmon; David F. Albertini; Norbert Gleicher (Journal of Ovarian Research, 2018)
Abstract Background Highly Individualized Egg Retrieval (HIER), defined as age-specific early oocyte retrieval (ER), has been demonstrated to avoid premature luteinization in women ≥43. We here investigated whether HIER also applies to younger women with premature ovarian aging (POA), and what best lead follicle size should be for administration of ovulation-triggers. Methods Fifty-six women ≥43, and 37 POA patients underwent IVF cycles. Granulosa cells (GCs) were isolated, cultures were established, RNA was extracted and real-time PCR analyses performed, with gene expressions at mRNA level investigated for FSH receptor (FSHR), luteinizing hormone receptor (LHCPR), P450 aromatase (CYP19a1) and progesterone receptor (PGR). POA was defined by age < 40, FSH above 95%CI and/or AMH below 95%CI for age. Women ≥43 years were divided into very early retrieval (VER), with human chorionic gonadotropin (hCG) trigger at 13.5–15.5 mm, ER at 16.0–18.0 mm or standard retrievel (SR) at 18.5–20.5 mm; POA patients were divided into ER and SR. Pregnancy rates and and molecular markers of premature luteinization (PL) were main outcome measures. Results ER resulted in a significantly higher clinical pregnancy rate (16.7%) than VER (5.9%) or SR (6.7%; both P < 0.05). Molecular markers of PL were highest with SR and lowest with VER. In POA, ER improved pregnancy chances even more than in women ≥43 (7.7% with SR vs. 41.7% with ER), while also reducing molecular markers of PL. With low ovarian reserve (LOR), by avoiding PL, ER with hCG trigger at 16.0–18.0 mm, thus, improves clinical pregnancy rates at all ages. As VER demonstrated lowest molecular PL marker but equally poor pregnancy rates as SR, too early ovulation triggers, likely, result in cytoplasmatic immaturity. Conclusions HIER is even more effective in POA patients than women above age 43, demonstrating that HIER should be further investigated going into even more advanced ages.